Carbon metabolic homogenization is linked to microbial competition and antimicrobial resistance in soils under forest-to-cropland conversion - Zhang, Shaoyang; Zhang, Tianlun; Du, Shuai; Yang, Zhugen; Liu, Shengen; Zhou, Guiyao; Delgado-Baquerizo, Manuel; Zhu, Dong (Elsevier, 2026)
Global agricultural expansion by converting natural forests into croplands often leads to soil functional homogenization and antimicrobial resistance enhancement, threatening ecosystem services. However, the associations between microbial carbon metabolic homogenization and antimicrobial resistance remain largely unknown. Here, we collected 240 paired forest and cropland soil samples from the most intensively farmed Yangtze River Basin in China, and constructed a novel framework based on microbial functional traits to decipher the role of carbon metabolic homogenization on antimicrobial resistance via microbial competition for metabolites. Using genome-scale metabolic models, we found that carbon metabolic homogenization was associated with a shift in microbial interactions from cooperation toward competition, with a 45.6% increase in competitive interactions that coincided with a 35.6% higher antimicrobial resistance gene (ARG) diversity. This shift was accompanied by smaller genome sizes and higher 16S rRNA copy numbers, indicating fast-growing, resource-acquisitive microbial strategies. Metabolic transfer analyses further revealed less cooperation relationships among microbial communities in cropland soils than in forest soils, indicating an intensified battle for communal metabolites and an attenuated exchange for complementary metabolites. Together, these findings provide a new framework to understand the association between carbon metabolic homogenization and soil antimicrobial resistance risks from the perspective of microbial traits and interactions under land use change.
Keywords: Soil functional homogenization; Microbial carbon metabolism; Antimicrobial resistance genes; Microbial competition; Land-use change; Antimicrobial Resistance; Infectious Diseases; Emerging Infectious Diseases; 15 Life on Land; Strategic, Defence & Security Studies; 34 Chemical sciences; 40 Engineering; 41 Environmental sciences; Soil Microbiology; Carbon; Forests; China; Bacteria; Agriculture; Soil; RNA, Ribosomal, 16S; Drug Resistance, Microbial; Crops, Agricultural